Traumatic rupture of jejunal burkitt's lymphoma with intestinal transection - Anoop Singh; Girish Prabhakar (Wolters Kluwer Medknow Publications, 2019)
Burkitt's lymphoma (BL) is an aggressive non-Hodgkin lymphoma.[1] BL of the small intestine, presenting as a surgical emergency needing emergency laparotomy, is an uncommon presentation of this tumor. We present a case of BL presenting as perforation peritonitis after blunt trauma abdomen.